Theory of Pools of Consciousness as a Tool for Critical Analysis of Public Discourse - Polak, Beata Anna (Sensus Historiae, 2024)
This article is an extended presentation of the “consciousness pools” methodology as a new methodological proposal within the framework of Critical Discourse Analysis (initially developed together with Tomasz Polak as part of the analysis of the church-state discourse in Poland in the years 1945–2013). This methodology is used to analyze strongly ideological discourses, be it religious, political or cultural. The author presents three “awareness pools” controlling this type of discourses: the pool of attractions, the pool of consolidation and the pool of trauma. The concept of pools is taken over from the sociological analysis of material “common pools;” however, its application is transferred to the analysis of consciousness resources.